Práticas estruturantes e de mercado na construção do impacto em sustentabilidade: os processos de translação e inscrição na produção de café certificado no contexto sul-mineiro - Souza, Cássio Eduardo Cândido (2019)
Coffee market is a dynamic segment of the global economy and congregates several actors of the supply chain in different interaction and relationship levels to make the trading of this product viable. One of the components that is form such product’s value and which is becoming more and more notorious is sustainability and the respect to socio-environmental issues at the coffee producing origin, an aspect which becomes relevant for the final consumer. Aiming to address these concerns, coffee sector is adopting third party voluntary certification schemes as alternatives to compose their sustainable product portfolio. The objective is to offer to consumers with the information that these so-called sustainable products improve management, social and environmental conditions of the farms in which they are implemented. The action of the consumer to demand a sustainable product; the action of the industry to alter a governance structure; and the action of the producer to voluntarily certify are examples on how these actions carried out by different actors in a market impact in another’s actions, creating unique market arrangements and structures. Using the Market Making as theoretical basis this paper aimed to identify how the market practices (transaction, representation and normative) conducted by UTZ provoke translations in the production system structure of small coffee growers, being able to alter their management, agronomical, social, environmental and governance activities, in a group of certified producers associated to a cooperative in southern Minas Gerais region. By carrying out of interviews with certified producers, analyzing the group formation process, its characteristics and Managing Unit performance through category content analysis it was possible to infer that market practices conducted by UTZ alter market practices conducted by the Managing Unit as well as by the producers. As main results, producers mentioned the operation, aesthetic and vision transformations as main benefits of UTZ, ranking discipline to carry certification processes out as main challenge, being able to indicate how the practices of farm conduction were prior and after certification, besides the alterations of several philosophical and relational aspects entailed along the certification process. It is identified that not only UTZ but producers and group certification Managing Unit conduct market practices and structuring practices, being possible to infer that inscription processes are relevant to allow the transport of one same-natured market practice conducted by an actor to a second actor’s perspective, and that these processes are facilitated by the Structuring Practices these actors insert in the market aiming to promote assimilations or dissociations of these inscriptions. The market practices conducted by UTZ, Managing Unit and Producer interact among each other, through inscription processes, which lead to translation chains, overflowing the market through these asymmetries, and framing the market with the assimilation of these inscriptions. Therefore, the proposed elements by Market Making, as well the ordering relationships based on Market Practices grant dynamism to the market.